2012
DOI: 10.1017/s0007114512002607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding Bt MON810 maize to sows during first gestation and lactation on maternal and offspring health indicators

Abstract: A total of twenty-four sows and their offspring were used in a 20-week study to investigate the effects of feeding GM maize on maternal and offspring health. Sows were fed diets containing GM or non-GM maize from service to the end of lactation. GM maize-fed sows were heavier on day 56 of gestation (P, 0·05). Offspring from sows fed GM maize tended to be lighter at weaning (P¼ 0·08). Sows fed GM maize tended to have decreased serum total protein (P¼ 0·08), and increased serum creatinine (P,0·05) and g-glutamyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…According to Winnicka (29), average values of estimated blood indices are located in the range typical for healthy adult swine. These results remain in agreement with findings of Walsh's et al (27), who showed that feed mixture containing MON810 maize did not influence the biochemistry and haematological indices in sows and their offspring. Another experiment by Walsh et al (28), carried out on weaned piglets receiving GM maize for 80 or 110 d, did not confirm any effect of the diet on basic haematological indices (erythrocyte count, erythrocyte parameters, haemoglobin concentration, and haematocrit).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to Winnicka (29), average values of estimated blood indices are located in the range typical for healthy adult swine. These results remain in agreement with findings of Walsh's et al (27), who showed that feed mixture containing MON810 maize did not influence the biochemistry and haematological indices in sows and their offspring. Another experiment by Walsh et al (28), carried out on weaned piglets receiving GM maize for 80 or 110 d, did not confirm any effect of the diet on basic haematological indices (erythrocyte count, erythrocyte parameters, haemoglobin concentration, and haematocrit).…”
Section: Discussionsupporting
confidence: 93%
“…Piglets rearing indices also remained unchanged. The studies conducted by Walsh et al (27) on sows receiving mixtures with GM or not-GM maize showed a similar body weight at the beginning and at the end of pregnancy, as well as a similar backfat thickness for both treatments. Moreover, the average daily body weight gains of their nursing progeny were not affected by maternal feeding.…”
Section: Discussionmentioning
confidence: 86%
“…Significantly higher plasma activities of ALT were seen in female rats fed GM (GNA) rice . Minimal effects were also reported (Walsh et al, 2013) where ALT and AST were also slightly increased in sows fed on GM maize during gestation. ALT and AST activity was slightly altered in mice fed on GM soybean compared to a non-GM diet (Malatesta et al, 2002).…”
Section: Discussionmentioning
confidence: 82%
“…Although no difference was observed in fecal Lactobacillus counts using traditional culturing methods, this can be attributed to the inability of culture-based approaches to account for unculturable lactobacilli (40). Lower intestinal Lactobacillus counts would generally be perceived as negative as this genus is considered to have a beneficial role in the porcine, as well as the human, intestine (41,42); however, no health abnormalities were observed in the sows (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…All diets were formulated to meet or exceed the National Research Council requirements for pigs at each production stage (23). Details of animal feeding have previously been described by Walsh et al (21) and Buzoianu et al (22).…”
Section: Pig Feeding Studymentioning
confidence: 99%